Tetrahydrobiopterin improves cardiac and pulmonary function after cardiopulmonary bypass - Szabó, Gábor; Seres, Leila; Soós, Pál; Gorenflo, Matthias; Merkely, Béla; Horkay, Ferenc; Karck, Matthias; Radovits, Tamás (European journal of cardio-thoracic surgery, 2011)
Objective: Tetrahydrobiopterin (BH4) is an important cofactor of endogenous nitric oxide synthesis. In the present preclinical study, we investigated the effects of BH4 on cardiac and pulmonary function during early reperfusion in an experimental model of cardioplegic arrest and extracorporal circulation. Methods: Twelve anesthetized dogs underwent hypothermic cardiopulmonary bypass. After 60 min of hypothermic cardiac arrest, reperfusion was started after application of either saline vehicle (control, n = 6), or BH4 (n = 6). Left-ventricular end-systolic pressure volume relationship (Ees) was measured by a combined pressure-volume conductance catheter at baseline and after 60 min of reperfusion. Left anterior descending (LAD) coronary (CBF) and pulmonary blood flow (PBF), endothelium-dependent vasodilatation to acetylcholine (ACh), endothelium-independent vasodilatation to sodium nitroprusside (SNP) and alveolo-arterial O2 gradient were determined. Results: The administration of BH4 led to a significantly better recovery of Ees (given as percent of baseline: 85 ± 22 vs 46 ± 15%, p ≪ 0.05). CBF was also significantly higher in the BH4 group (38 ± 5 vs 22 ± 5 ml min−1, p ≪ 0.05). While the vasodilatatory response to SNP was similar in both groups, injection of ACh resulted in a significantly higher increase in CBF (64 ± 12 vs 25 ± 12%, p ≪ 0.05) and PBF (49 ± 15 vs 36 ± 14%, p ≪ 0.05) in the BH4-treated animals. Alveolo-arterial O2 gradient was significantly lower after BH4 supplementation (80 ± 15 vs 49 ± 14 mmHg, p ≪ 0.05). Conclusions: Application of BH4 improves myocardial, endothelial and pulmonary function after cardiopulmonary bypass with hypothermic cardiac arrest. The observed protective effects indicate that BH4 could be a novel therapeutic option in the treatment of ischemia/reperfusion injury.